Effects of the GABA‐uptake blocker NNC‐711 on spontaneous sharp wave–ripple complexes in mouse hippocampal slices. Issue 5 (5th March 2013) - Viereckel, Thomas; Kostic, Milos; Bähner, Florian; Draguhn, Andreas; Both, Martin
Abstract The precise temporal and spatial activity patterns of neurons in cortical networks are organized by different state‐dependent types of network oscillations. GABAergic inhibition plays a key role in the underlying mechanisms of such oscillations and it has been suggested that the duration of widely distributed phasic inhibitory postsynaptic potentials (IPSPs) determines the frequency of the resulting network oscillation. Here, we test this hypothesis in an in vitro model of sharp wave–ripple (SPW‐R) complexes, a particularly fast pattern of network oscillations at ∼200 Hz which is involved in memory consolidation. We recorded SPW‐R in mouse hippocampal slices in the absence and presence of NCC‐711, an inhibitor of GABA uptake. The resulting prolongation of IPSP resulted in reduced occurrence of SPW‐R, whereas the superimposed fast oscillations as well as the precision of rhythmic cell synchronization remained stable. Application of Diazepam which is a positive modulator of the GABAA receptor led to consistent results. We conclude that phasic inhibition is a major regulator of network excitability in CA3 (where SPW‐Rs are generated), but does not set the frequency of hippocampal ripples. © 2013 Wiley Periodicals, Inc.